A convolutional neural network based model with improved activation function and optimizer for effective intrusion detection and classification - Kabir, Solaiman; Sakib, Sadman; Hossain, Md. Akib; Islam, Safi (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.